MODERNIZATION OF THE COMPANY’S STRATEGY IN THE CONDITIONS OF INNOVATIVE CHANGES - Тимофеєв, Владислав О. (Journal of Strategic Economic Research, 2024)
In the presented work, it is noted that in the modern dynamic business environment, which is characterized by the rapid pace of innovation and technological changes, the modernization of the company’s strategy becomes a key factor of success and competitiveness. Innovative changes, such as the development of new technologies, changes in consumer preferences, the introduction of digital solutions and the globalization of markets, significantly affect the business environment and require companies to quickly adapt and make strategic transformations. Attention is also focused on the fact that the modernization of the company’s strategy in the conditions of innovative changes is a complex process that involves reviewing and adjusting existing strategic plans to maximize the use of new opportunities and overcome emerging challenges. This includes adaptation to new technological realities, rethinking business models, as well as updating approaches to managing resources, products and services. The purpose of the presented work is to determine the main components of the company’s strategy in the conditions of innovative changes. The main methods presented in the work are: the synthesis method, the generalization method, the logical method, the graphic method, which allowed to visually display the main elements of the research, the analysis method. The presented methods made it possible to justify the purpose of the study and to determine the main aspects of the modernization of the company’s strategy in the conditions of innovative changes. It is determined that the strategy modernization process can be caused by a number of factors, among which the key ones are: the introduction of new technologies that change the methods of production and customer service; changes in market conditions requiring new approaches to business planning and management; as well as increasing requirements for sustainability and social responsibility of companies. The importance of strategy modernization is due to the need not only to maintain competitiveness in modern markets, but also to ensure long-term development and sustainability of business. Understanding innovative trends, their impact on business processes and market opportunities allows enterprises not only to adapt to changes, but also to use them to their advantage, gaining additional advantages in the competition. That is why, we note that the modernization process requires a comprehensive approach, which includes the assessment of new opportunities, the development and implementation of innovative solutions, as well as flexible change management to ensure adaptation to the rapidly changing business environment.